Revision of Australian Tomosvaryella Aczél (Diptera: Pipunculidae) with description of 100 new species - Motamedinia, Behnam; Földvari, Mihaly; Skevington, Jeffrey H.; Kelso, Scott (Zootaxa, 2025)
A comprehensive taxonomic revision of genus Tomosvaryella Aczél, 1939 (Diptera: Pipunculidae: Tomosvaryellini) from Australia is provided, based on morphological characters and barcode sequence data from mitochondrial COI. One hundred new species are introduced to science, the previously known six species are redescribed and lectotypes are nominated where required. Descriptions of all species, distribution maps, diagnoses, an illustrated key, some comments about taxonomic status and genetic distance are given.